2017
DOI: 10.1038/s41598-017-06280-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased overall cortical connectivity with syndrome specific local decreases suggested by atypical sleep-EEG synchronization in Williams syndrome

Abstract: Williams syndrome (7q11.23 microdeletion) is characterized by specific alterations in neurocognitive architecture and functioning, as well as disordered sleep. Here we analyze the region, sleep state and frequency-specific EEG synchronization of whole night sleep recordings of 21 Williams syndrome and 21 typically developing age- and gender-matched subjects by calculating weighted phase lag indexes. We found broadband increases in inter- and intrahemispheric neural connectivity for both NREM and REM sleep EEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The firing rate was larger in WT animals, and the significant windows are indicated above with a black line (p < 0.05) high integration capacity (lower path length) and low segregation levels (modularity); alterations that are especially notorious at gamma-like frequency bands. These results are in agreement with previous findings in humans reporting increased overall cortical connectivity [11] and suggest that the cognitive deficits previously reported in this murine model of WBS [26] may be associated with the interruption of the equilibrium between integration and segregation at gamma frequencies. The abovementioned alterations in the morphology and number of dendritic spines at the level of the frontal cortex might explain, at least partially, the origin of these functional abnormalities, which may hamper the capacity of the cortical network to distribute and integrate information in order to execute specialized functions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The firing rate was larger in WT animals, and the significant windows are indicated above with a black line (p < 0.05) high integration capacity (lower path length) and low segregation levels (modularity); alterations that are especially notorious at gamma-like frequency bands. These results are in agreement with previous findings in humans reporting increased overall cortical connectivity [11] and suggest that the cognitive deficits previously reported in this murine model of WBS [26] may be associated with the interruption of the equilibrium between integration and segregation at gamma frequencies. The abovementioned alterations in the morphology and number of dendritic spines at the level of the frontal cortex might explain, at least partially, the origin of these functional abnormalities, which may hamper the capacity of the cortical network to distribute and integrate information in order to execute specialized functions.…”
Section: Discussionsupporting
confidence: 93%
“…Alterations in specific patterns of neuronal synchronization are characteristic of different neuropsychiatric and neurodevelopmental conditions [45,46]. Indeed, previous studies in WBS patients have shown alterations in the overall level of cortical coherence [10,11]. Thus, in order to test whether the alterations in synchronization we observed at the level of the frontal areas were a general phenomenon that could be affecting the integrity of the cortical network in our mouse model, we next studied the overall functional connectivity of the cortical network.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The lack of statistical significance prevents interpretation of the observed attenuated alpha power in the WS group, however attenuated full- and low-alpha compared to the CA and MA groups was predicted based on the existing literature with other developmental disorders with attentional deficiencies including FXS [ 59 ], DS [ 56 ], and ADHD [ 57 , 82 , 83 ]. In WS, significantly attenuated alpha power has been observed in research using combined EC/EO data [ 67 ], and in sleep states [ 64 , 65 ]. In ADHD, attenuated alpha power during resting states is thought to reflect an ongoing state of cortical hyper-arousal even in the absence of cognitive processing [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While other types of motor skills certainly need to be also mapped in this regard, its applications may be useful in educational settings and during career planning before adolescence. Furthermore, the present phenomena should be examined in atypical development since there are neurodevelopmental disorders such as autism spectrum disorder (Oldehinkel et al 2019), attention deficit hyperactivity disorder (Bos et al 2017) and rare disorders (Gombos, Bódizs, and Kovács 2017) that involve both atypically developing long-range brain networks including motor subsystems and altered hand function (Berencsi, Gombos, and Kovács 2016;Rommelse et al 2007;Travers et al 2017).…”
Section: Discussionmentioning
confidence: 99%